2022
DOI: 10.3389/fmed.2022.815799
|View full text |Cite
|
Sign up to set email alerts
|

High-Flow vs. Low-Flow Nasal Cannula in Reducing Hypoxemic Events During Bronchoscopic Procedures: A Systematic Review and Meta-Analysis

Abstract: IntroductionHigh-flow nasal cannula (HFNC) oxygenation method has been proven to be successful in oxygenation of patients with respiratory failure and has exhibited clinical superiority compared to low-flow nasal cannula (LFNC).MethodsWe performed a systematic review and meta-analysis to evaluate the potential favorable impact of HFNC oxygenation during bronchoscopy and related procedures like endobronchial ultrasound-transbronchial needle aspiration. Only randomized control trials (RCTs) were included in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 41 publications
(100 reference statements)
0
14
0
Order By: Relevance
“…To the best of our knowledge, this is the first report of the optimal oxygen flow rate for HFNC to prevent desaturation during bronchoscopy. Although several studies have reported that HFNC can reduce the incidence of desaturation during bronchoscopy, 2 , 7 11 none reported an ideal oxygen flow rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first report of the optimal oxygen flow rate for HFNC to prevent desaturation during bronchoscopy. Although several studies have reported that HFNC can reduce the incidence of desaturation during bronchoscopy, 2 , 7 11 none reported an ideal oxygen flow rate.…”
Section: Discussionmentioning
confidence: 99%
“…As compared to conventional therapy, HFNC can reduce the incidence of hypoxemia during sedation for bronchoscopy. 2 , 7 11 However, there is currently no consensus on an optimal flow rate. We hypothesized that increasing the oxygen flow rate can prevent desaturation during bronchoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…FOB is a fundamental diagnostic and therapeutic procedure in the assessment of the airways and lung parenchyma. It is an interventional technique that, like all procedures, can be associated with complications, including the development of hypoxaemia [ 6 , 7 , 8 , 10 , 11 , 27 , 28 ]. Hypoxaemia can also lead to serious cardiac events such as atrial or ventricular arrhythmias [ 8 ].…”
Section: Hfnc In Fobmentioning
confidence: 99%
“… Other circumstances that arise during fiberoptic bronchoscopy (FOB) include: The effective airway diameter is reduced when advancing the bronchoscope beyond the glottis; suctioning during FOB can result in alveolar recruitment loss and atelectasis formation. Instillation of local anesthetics or saline solution during certain procedures, such as bronchoalveolar lavage (BAL), may cause alveolar flooding and affect the ventilation/perfusion ratio [ 6 , 7 , 8 , 9 ]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation